Effectiveness of Antiemetic Regimens for Highly Emetogenic Chemotherapy‐Induced Nausea and Vomiting: A Systematic Review and Network Meta‐Analysis. (17th October 2018) - Yokoe, Takamichi; Hayashida, Tetsu; Nagayama, Aiko; Nakashoji, Ayako; Maeda, Hinako; Seki, Tomoko; Takahashi, Maiko; Takano, Toshimi; Abe, Takayuki; Kitagawa, Yuko
Abstract: Background: It is important to control chemotherapy‐induced nausea and vomiting (CINV) to maintain dose intensity and patients' quality of life. The National Comprehensive Cancer Network guidelines suggest combination therapy of antiemetic agents. The growing number of antiemetic regimens, and in particular the growing use of regimens containing antagonists to the Nk‐1 receptor (NK1RAs) and the antipsychotic drug olanzapine (OLZ), call for the re‐evaluation of the optimal regimen for CINV. This study assessed the efficacy and safety of antiemetic regimens for highly emetogenic chemotherapy, using Bayesian network meta‐analysis. Methods: Randomized trials that compared different antiemetic regimens were included. We strictly followed Preferred Reporting Items for Systematic Reviews and Meta‐Analysis guidelines. The main outcomes were the odds ratio (OR) for overall complete response (absence of vomiting). We conducted network meta‐analysis within a Bayesian model to combine the direct and indirect evidence. Safety was assessed from the trial description. All statistical tests were two‐sided. Results: We systematically reviewed 27 randomized control trials (13, 356 participants), which compared 12 different antiemetic regimens: serotonin‐3 receptor antagonist (5HT3), 5HT3 + dexamethasone (Dex), palonosetron (PAL), PAL + Dex, PAL at 0.75 mg (PAL0.75), PAL0.75 + Dex, NK1RA + 5HT3 + Dex, NK1RA + PAL + Dex, an oral combination of netupitant and palonosetron (NEPA) + Dex, OLZ + 5HT3 + Dex, OLZ + PAL + Dex, and OLZ + NK1RA + 5HT3 + Dex. An NK1RA + 5HT3 + Dex regimen and an NK1RA + palonosetron + Dex regimen gave a higher complete response (CR) rate than the reference regimen, 5HT3 + Dex (OR, 1.75; 95% credibility interval [95% CrI], 1.56–1.97, and OR, 2.25; 95% CrI, 1.66–3.03, respectively). A regimen containing NEPA was more effective in producing CR than conventional regimens without NEPA or olanzapine. Further analysis, based on the surface under the cumulative ranking probability curve, indicated that olanzapine‐containing regimens were the most effective in producing CR. Conclusion: Our meta‐analysis supports the conclusion that olanzapine‐containing regimens are the most effective for CINV of highly emetogenic chemotherapy. We confirmed that NK1RA + PAL + Dex is the most effective of conventional regimens. Substituting olanzapine for an Nk‐1 receptor antagonist may offer a less costly and more effective alternative for patients. Abstract : The growing number of antiemetic regimens calls for a definition of the optimal regimen for chemotherapy‐induced nausea and vomiting (CINV). This meta‐analysis was conducted for direct and indirect comparisons of multiple randomized clinical trials to assess the efficacy and safety of antiemetic regimens for CINV of highly emetogenic chemotherapy.